The Effect of Murabahah and Mudharabah Financing on Profitability with NonPerforming Financing (NPF) as a Moderating Variable (at Islamic Commercial Banks in Indonesia) - Ismawati; M. Alfira Yuningsih; Kamaruddin; Samsul Arifai (UIN Mataram, 2021)
This study aims to determine the effect of Murabahah and Mudharabah financing on profitability with Non Performing Financing (NPF) as a moderating variable in Islamic commercial banks in Indonesia for the 2013-2019 period. The population used is all Islamic Commercial Banks registered with the Financial Services Authority as many as 14 Islamic Banks. The sampling technique used was the purposive sampling method, and 8 samples were selected. This research is a type of quantitative research using Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA). The results of the study state that Murabahah financing has a negative and significant effect on ROA, Mudharabah financing has a positive and significant effect on ROA, Non-Performing Financing (NPF) does not moderate the relationship between Murabahah financing and ROA and Non-Performing Financing (NPF) has a significant influence on moderating the financing relationship. Mudharabah on ROA.